(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
The unique position and place of each nation in the world community does not depend on the number of its population. Rather, the ability to manifest national characteristics, the knowledge of the representatives of the nation of their homeland, history, material and spiritual monuments and their ability to show them to the world determine their status in the international arena. We all know that from the first days of our country’s independence, terms such as "values", "national idea", "self-awareness", "national revival", "social justice", "national consciousness", "national pride", "national pride", "Patriotism" have appeared in all aspects of our life. These terms have been encouraging our people to act in unity and solidarity towards one goal: "A free and prosperous homeland, a free and prosperous life". After all, independence also means the awareness of national identity. In our country, a person and his life are considered the highest value. Since the emergence of humanity, his dignity, honor, and noble views have been glorified. Therefore, respecting the dignity and worth of a person, developing his living conditions, knowledge, and cultural and educational level, improving his health, and protecting his life are among the priority areas of our state policy, and this is also stated in our main dictionary: “The state expresses the will of the people and serves their interests.” This is precisely the essence of the changes, reforms, and laws and regulations being adopted in our country today. Our national values ​​are also closely related to universal values. Universal values ​​are deep and comprehensive in scope and content, embodying the aspirations of all nations, peoples, and peoples. The more national values ​​are combined with universal human values, the greater the opportunity for their development and popularization.